A comprehensive study on the microstructure of plasma spraying coatings after electron beam remelting. Issue 1 (1st February 2023) - St Węglowski, M; Śliwiński, P; Dymek, S; Kalemba-Rec, I; Kapuściński, M; Wrona, A; Kustra, K
Abstract: One of the most popular thermal spraying technology is atmospheric plasma spraying (APS). However, it should be noted, that numerous imperfections in the APS surface layers can be occurred. The porosity, microcracks as well as lamellar microstructure occurred. Moreover, the adhesion of the coating is limited. However, the reduction of porosity and other imperfections by remelting process can be eliminated. The laser or electron beams for remelting are the most popular technologies. Mainly, power of the beam and travelling speed influence on the thickness and the final properties of the remelted coatings. In the paper, the electron beam (EB) process for remelting of plasma spraying surface layers in relation to microstructure is presented. The Ni20%Cr + 30%Re APS coating on stainless steel substrate 316Ti grade by electron beam was remelted. The effect of remelting process on microstructure was presented. The light microscopy (LM) as well as scanning electron microscopy (SEM) and energy disperse spectroscopy (EDS) for microstructure analysis of APS coatings after EB remelting were used. The results show that the APS coatings subjected EB remelted becomes much denser. Moreover, the porosity was reduced and the chemical composition of the coatings after remelting became homogeneous.